Safety and Adequacy of Kidney Biopsy Procedure in Patients with Obesity. Issue 1 (29th January 2023) - Qian, Long; Menez, Steven; Hu, David; Weinstein, Jason; Melchinger, Hannah; Thiessen-Philbrook, Heather; Luciano, Randy L.; Turner, Jeffrey M.; Perazella, Mark A.; Corona Villalobos, Celia Pamela; Shaw, Melissa M.; Wilson, F. Perry; et al.
Abstract : Key Points: Patients with obesity did not have any larger hematocrit drop after kidney biopsy compared with those without obesity. Patients with obesity had fewer glomeruli sampled from kidney biopsy compared with those without obesity. For patients with obesity, kidney biopsy is a safe procedure but may have lower diagnostic adequacy.